TÚRKIY XALÍQLAR ÁDEBIYATTANÍW ILIMINDE HAYAL-QÍZLAR DÓRETIWSHILIGINIŃ IZERTLENIWI - Aliyeva, X.R. (ILIM hám JÁMIYET, 2022)
The article examines the level of creativity of women in fiction, their place in literature, the content and educational significance of their works, as well as the study of female creativity in the literary criticism of the Turkic peoples.
Keywords: ádebiyatshunoslik; lirika; xotin-qizlar ijodi; lirik qahromon; xotin-qizlar lirikasi va b